The German model of risk distribution in supplementary occupational pensions. - Burger, C; Clark, G (School of Geography and the Environment (University of Oxford), 2010)
The German pension reform of 2001 was a milestone on the road towards pension individualisation. It enhanced the funded occupational (and private) pension system (Riester-pensions), and therefore shifted investment risks to employers and individuals. The new occupational scheme allows for different types of pension vehicles that are either defined benefit (DB) or defined contribution (DC) plans. Since all such schemes are embedded in multiple layers of institutional insurance mechanisms, including strict investment principles, even the riskier DC schemes have limited exposure to financial market volatility. This article explores the extent of risk individualisation in Riester-occupational pensions by describing risk distribution between the employee and the employer. It starts with discussing the relevant legislation since the nineteenth century until the reform of 2001. The reform defined two main risk-related decisions which are analysed here. The first, the selection of the pension vehicle, determines the scope of the risk. The second is the choice between DB and German DC that defines the distribution of risk between the employer and the employee. Finally, the paper investigates these choices empirically by using a unique, proprietary data-set of a German pension provider with approximately 271,000 pension scheme enrolees joining in the years between 2002 and 2008. The findings highlight the employer’s pivotal role in determining the options available to the employee. For this reason, employee’s choice is limited and could partly be explained by socio-economic variables traditionally associated with risk aversion. Furthermore, despite the low level of risk embedded in Riester-type occupational pensions, individuals prefer the low risk alternatives. The study also identifies a conscious, risk prone group of employees who joined the savings plan right after the reform, in 2002 and 2003. Enrolees of the latter years are more likely to prefer insurance over uncertain returns, and reject the idea of risk individualisation.